Plant-based bioactive glass and application thereof in oral care products
By modifying bioactive glass and polyamide-amine-type dendrimers with specific particle size distribution, combining licorice extract and Magnolia extract, the problem of poor tooth remineralization effect in the prior art is solved. , realizes efficient remineralization and cleaning of teeth, and improves teeth brightness and oral health.
Patent Information
- Application Number
- CN202411182776.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-01-14
AI Technical Summary
The existing plant-based bioactive glass has a small amount of mineral residue on the tooth surface and the cured layer formation is slow, which is not effective in tooth restoration, making it difficult to safely and gently realize tooth remineralization and caries prevention.
Modified bioactive glass of plant extracts with specific particle size distributions, prepared by mixing and drying with phosphate buffer to form modified bioactive glass including licorice extract and Magnolia extract, combined with polyamide-amine-type branches , and promotes remineralization and cleaning of teeth surfaces.
It significantly improves the remineralization effect of teeth, microhardness recovery rate, dentin tubular closure rate and tooth brightness, reduces tooth sensitivity and exogenous pigmentation, and enhances oral health status.
Smart Images

Figure BDA0005013654400000131 
Figure BDA0005013654400000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of oral care, and in particular to a plant-based bioactive glass and an application thereof in oral care products. Background Art
[0002] Tooth enamel is the most calcified and hardest part of the tooth. It wraps around the outside of the crown and is about 2 to 2.5 mm thick. Its main component is inorganic matter, which can serve as a protective layer for the teeth. When acidic foods are consumed for a long time, the tooth enamel will be eroded by acid. Over time, it will cause the enamel to demineralize and expose the dentin. In addition, excessive intake of fat and sugar will also cause bacteria to grow and form dental plaque on the surface of the damaged enamel. Since tooth enamel cannot repair itself, it will cause oral problems such as caries and tooth sensitivity.
[0003] As people's living standards improve, their attention to oral health has greatly increased. Currently, fluoride is often used to prevent tooth decay and promote enamel remineralization, but existing studies have shown that long-term exposure to excessive fluoride can cause problems such as fluorosis. Therefore, how to safely, gently and effectively repair tooth enamel has gradually become a research hotspot.
[0004] Plant-based bioactive glass is a bioactive material that can undergo physical and chemical reactions with dental tissues. It has good biocompatibility with dental bone tissue and soft tissues and has a basis for application in oral care. However, existing experimental studies have shown that in actual applications, plant-based bioactive glass leaves very little mineral residue on the tooth surface, and the speed at which the solidified layer is formed by plant-based bioactive glass is very slow and the tooth repair effect is poor. Summary of the invention
[0005] In order to promote tooth surface remineralization and improve tooth whiteness, the present invention provides a plant-based bioactive glass and application thereof in oral care products.
[0006] In a first aspect, the present invention provides a plant-based bioactive glass, which adopts the following technical solution:
[0007] A plant-based bioactive glass, including plant extract-modified bioactive glass;
[0008] The particle size D of the plant extract modified bioactive glass meets the following conditions: the mass proportion of particles with a particle size D satisfying 0.5 μm ≤ D < 8 μm is 40%-50%, the mass proportion of particles with a particle size D satisfying 8 μm ≤ D < 20 μm is 30%-40%, and the mass proportion of particles with a particle size D satisfying 20 μm ≤ D < 50 μm is 10%-20%;
[0009] The plant extract modified bioactive glass is prepared by a method comprising the following steps: mixing the plant extract with a phosphate buffer solution and then standing the mixture, adding the bioactive glass to the obtained mixed solution, stirring the mixture to obtain a suspension, and drying the solid matter obtained after solid-liquid separation of the suspension to obtain the plant extract modified bioactive glass;
[0010] The plant extract comprises liquorice extract and magnolia bark extract; the mass ratio of the liquorice extract to the magnolia bark extract is 2-5:1-2.
[0011] Preferably, the portion of the plant extract modified bioactive glass whose particle size D satisfies 0.5μm≤D<8μm is recorded as particle A, and the particle size D50 of particle A is 0.8-1.2μm; the portion of the plant extract modified bioactive glass whose particle size D satisfies 8μm≤D<20μm is recorded as particle B, and the particle size D50 of particle B is 8-12μm; the portion of the plant extract modified bioactive glass whose particle size D satisfies 20μm≤D<50μm is recorded as particle C, and the particle size D50 of particle C is 44-45μm.
[0012] First, in the present invention, by selecting plant-modified bioactive glass with a suitable particle size and range, on the one hand, the particle size of the plant extract-modified bioactive glass (particle A) with a smaller particle size range is smaller than the average diameter of the dentinal tubules (about 2.5 μm), so it can enter the dentinal tubules to play a physical blocking role; and the plant extract-modified bioactive glass (particle B) with a medium particle size range reacts quickly on the tooth surface after contacting with saliva in the oral cavity, and ion exchange can occur within 2-3 minutes, and calcium ions and phosphate ions are continuously hydrolyzed, thereby inducing the precipitation layer to gradually crystallize and form a layer of minerals (the main component is hydroxyl radicals). On the other hand, the plant extract-modified bioactive glass (particle C) with a larger particle size range has higher strength and can be used as an abrasive (physical action) to clean the surface of demineralized teeth to reduce exogenous pigment deposition and improve the cleaning effect on teeth. Through the combination of the above physical and chemical actions, a two-pronged approach can significantly improve the microstructure of the surface of demineralized teeth, make the surface of demineralized teeth smooth, have better reflective effect, and improve the brightness of demineralized teeth.
[0013] Second, the present invention modifies the bioactive glass by using licorice extract and magnolia bark extract. The glycyrrhizin in the licorice extract and magnolia bark phenol in the magnolia bark extract can play a role in introducing hydroxyl groups and phenolic hydroxyl groups into the bioactive glass. The introduced hydroxyl groups and phenolic hydroxyl groups can combine with the protein calcium in the demineralized tooth enamel to form a cyclic chelate that is insoluble in acid and has a stable structure, so that the gaps between the crystals in the demineralized tooth enamel become smaller, thereby alleviating the degree of stimulation of the external environment on the teeth after tooth demineralization and reducing the sensitivity of the teeth; moreover, the glycyrrhizin polysaccharide in the licorice extract and the magnolia bark polysaccharide in the magnolia bark extract can react with the hydroxyl groups on the surface of the bioactive glass to form hydrogen bonds. The hydrogen bonds can inhibit the activity of matrix metalloproteinases and promote bionic remineralization by modifying dentin collagen, which helps to improve the repair effect of the plant extract-modified bioactive glass on demineralized teeth, make the surface of the demineralized teeth smooth, and have a better reflective effect, thereby further improving the brightness of the teeth.
[0014] Third, the present invention modifies the bioactive glass through licorice extract and magnolia bark extract. Glycyrrhizic acid and liquiritin in the licorice extract and magnolia bark extract in magnolia bark can produce anti-inflammatory and antibacterial effects on the oral cavity, and have a good repair effect on the oral mucosa, which helps to achieve a healthy oral environment, provides a stable and healthy environment for the remineralization of demineralized teeth, and significantly improves the health of the oral cavity.
[0015] Preferably, the concentration of the plant extract in the mixed solution is 80-150 mg / mL; the standing time is 25-35 min; 2.5-4 g of the bioactive glass is added to every 100 mL of the mixed solution; the temperature during stirring is 40-60° C., and the duration of the stirring process is 5-10 h.
[0016] Preferably, the suspension is centrifuged at a speed of 2000-3000 rpm for 5-8 min to achieve solid-liquid separation.
[0017] The plant extract modified bioactive glass prepared by the above method is helpful to obtain plant extract modified bioactive glass with a high content of loaded plant extract, thereby achieving the repair effect of plant-based bioactive glass on demineralized teeth to the greatest extent.
[0018] Preferably, it is characterized in that the content of the bioactive glass expressed as oxides is: SiO2 40mol%-50mol%, P2O5 5mol%-10mol%, CaO 22mol%-30mol%, Na2O 22mol%-30mol%.
[0019] By selecting bioactive glass with a suitable oxide content ratio as the raw material to prepare plant extract-modified bioactive glass, a more ideal calcium-phosphorus ratio can be obtained, which helps to improve the remineralization efficiency, thereby promoting remineralization and repair of tooth enamel, thereby further improving the repair effect of plant-based bioactive glass on demineralized teeth.
[0020] In a second aspect, the present invention provides an oral care product containing plant-based bioactive glass, which adopts the following technical solution:
[0021] An oral care product containing plant-based bioactive glass comprises a basic component and a repair component, wherein the mass of the repair component accounts for 10%-25% of the total mass of the oral care product; the repair component comprises the plant extract modified bioactive glass as described above.
[0022] Preferably, the repair component further comprises polyamide-amine type dendrimer.
[0023] Polyamide-amine dendrimers can work together with plant extract modified bioactive glass to affect the morphology and size of hydroxyapatite generated during the remineralization process. In addition, due to the good flexibility and high viscosity of polyamide-amine dendrimers, they can be confined to the surface of dentin and penetrate into the dentin tubules, forming a good chemical bond with positively charged hydroxyapatite, thereby further improving the toothpaste's repair effect on enamel. At the same time, polyamide-amine dendrimers can also effectively prevent bacteria from adhering to the surface of tooth tissue or biomaterials, interfering with the formation of bacterial biofilms, thereby working together with plant extract modified bioactive glass to significantly improve its antibacterial properties.
[0024] Preferably, based on the repair component, the mass ratio of the plant extract-modified bioactive glass to the polyamide-amine dendrimer in the repair component is 2-4:1.
[0025] By further optimizing the mass ratio of plant extract-modified bioactive glass to polyamide-amine dendrimer, it is possible to reduce the size of the gaps between crystals in enamel after demineralization while increasing the strength of the remineralization products filling the gaps, which helps to improve the repair effect of toothpaste on demineralized teeth.
[0026] Preferably, based on the basic components, the basic components include the following raw materials in parts by weight: 0.3-0.6 parts of thickener, 35-45 parts of humectant, 3-4 parts of foaming agent, 0.2-0.5 parts of sweetener, 0.5-1.2 parts of neutralizer, 20-35 parts of deionized water, and 2-5 parts of enhancer.
[0027] Preferably, the sweetener comprises at least one of aspartame, xylitol, saccharin sodium, aspartame and stevioside; and the neutralizer comprises sodium citrate.
[0028] Preferably, the thickener includes at least one of carrageenan, carboxymethyl cellulose, starch, xanthan gum, gum arabic, gum karaya, and carrageenan; the humectant includes at least one of glycerin, sorbitol, propylene glycol, polyethylene glycol, and polypropylene glycol; the foaming agent includes at least one of cocamidopropyl betaine and sodium lauryl sulfate; and the enhancer includes hydroxyapatite.
[0029] Hydroxyapatite helps promote the repair of demineralized teeth by plant-based bioactive glass, strengthens the bonding of ions, and improves the remineralization effect of demineralized teeth.
[0030] Preferably, the oral care product comprises any one of toothpaste, tooth protection paste, oral antibacterial paste, oral desensitizing paste, oral anti-caries paste, and tooth desensitizer.
[0031] Preferably, based on the basic component, the basic component further includes 20-35 parts of abrasive; the abrasive includes at least one of silicon dioxide and calcium carbonate.
[0032] By combining abrasives with reinforcing agents, the abrasives can work with plant-based bioactive glass to improve the cleaning of teeth and enhance tooth brightness. DETAILED DESCRIPTION
[0033] For better understanding and implementation, the technical solution of the present invention will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0035] Unless otherwise indicated, all numerical values expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.
[0036] As used herein, "and / or" means one or all of the mentioned elements.
[0037] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.
[0038] All percentages in the present invention are by weight, unless otherwise specified.
[0039] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.
[0040] Example 1
[0041] 1. Preparation of plant extract modified bioactive glass
[0042] The plant extract (the mass ratio of licorice extract to magnolia bark extract is 3:2) was mixed with phosphate buffer and allowed to stand for 30 minutes to obtain a mixed solution with a plant extract concentration of 100 mg / mL; 3 g of bioactive glass (oxide content of SiO2 45 mol%, P2O5 8 mol%, CaO25 mol%, Na2O 22 mol%) was added to every 100 mL of the mixed solution and the two were mixed, and then stirred at 50°C for 8 hours to obtain a suspension; the obtained suspension was centrifuged at a speed of 3000 rpm for 5 minutes, and the solid matter obtained was dried to obtain plant extract modified bioactive glass;
[0043] The part of the plant extract modified bioactive glass whose particle size D satisfies 0.5 μm ≤ D < 8 μm is recorded as particle A, the part of the plant extract modified bioactive glass whose particle size D satisfies 8 μm ≤ D < 20 μm is recorded as particle B, and the part of the plant extract modified bioactive glass whose particle size D satisfies 20 μm ≤ D < 50 μm is recorded as particle C;
[0044] By mixing particles A (particle size D50 = 0.8 μm) with a mass proportion of 45%, particles B (particle size D50 = 10 μm) with a mass proportion of 35%, and particles C (particle size D50 = 45 μm) with a mass proportion of 20%, plant-based bioactive glass (referred to as Elopas plant-based bioactive glass) is obtained.
[0045] 2. Preparation of Toothpaste
[0046] Toothpaste includes basic ingredients and repair ingredients;
[0047] The mass of the basic components accounts for 82% of the total mass of the toothpaste, and the basic components include the following raw materials in parts by weight: 20 parts of silicon dioxide, 3 parts of hydroxyapatite, 10 parts of calcium carbonate, 0.2 parts of carrageenan, 0.2 parts of carboxymethyl cellulose, 15 parts of glycerol, 25 parts of sorbitol, 3 parts of cocamidopropyl betaine, 0.2 parts of aspartame, 0.1 parts of xylitol, 0.8 parts of sodium citrate, and 30 parts of deionized water;
[0048] The mass of the repairing component accounts for 18% of the total mass of the toothpaste, and the repairing component is the above-mentioned plant-based bioactive glass.
[0049] The toothpaste is prepared by the following steps:
[0050] Step 1, mixing carrageenan, carboxymethyl cellulose, aspartame, xylitol, glycerol, sorbitol and deionized water to obtain a first premix;
[0051] Step 2, mixing silicon dioxide and calcium carbonate with the first premix solution, stirring and heating to 60° C. to obtain a second premix;
[0052] Step 3: Mix and stir the plant extract-modified bioactive glass, cocamidopropyl betaine and the second premix, continue to add sodium citrate, and stir to obtain toothpaste.
[0053] Example 2
[0054] 1. Preparation of plant extract modified bioactive glass
[0055] The plant extract (the mass ratio of licorice extract to magnolia bark extract is 5:1) was mixed with phosphate buffer and allowed to stand for 25 minutes to obtain a mixed solution with a plant extract concentration of 80 mg / mL; the two were mixed according to the principle of adding 2.5 g of bioactive glass (oxide content of SiO2 50 mol%, P2O5 5 mol%, CaO 22 mol%, Na2O 23 mol%) per 100 mL of the mixed solution, and then stirred at 60°C for 5 hours to obtain a suspension; the obtained suspension was centrifuged at a speed of 2000 rpm for 8 minutes to obtain a solid substance, which was dried to obtain plant extract modified bioactive glass;
[0056] The part of the plant extract modified bioactive glass whose particle size D satisfies 0.5 μm ≤ D < 8 μm is recorded as particle A, the part of the plant extract modified bioactive glass whose particle size D satisfies 8 μm ≤ D < 20 μm is recorded as particle B, and the part of the plant extract modified bioactive glass whose particle size D satisfies 20 μm ≤ D < 50 μm is recorded as particle C;
[0057] By mixing particles A (particle size D50 = 1.2 μm) with a mass proportion of 40%, particles B (particle size D50 = 8 μm) with a mass proportion of 40%, and particles C (particle size D50 = 44 μm) with a mass proportion of 20%, plant-based bioactive glass (referred to as Elopas plant-based bioactive glass) is obtained.
[0058] 2. Preparation of Toothpaste
[0059] Toothpaste includes basic ingredients and repair ingredients;
[0060] The mass of the basic components accounts for 75% of the total mass of the toothpaste, and the basic components include the following raw materials in parts by weight: 20 parts of silicon dioxide, 2 parts of hydroxyapatite, 0.3 parts of carrageenan, 0.1 parts of starch, 0.2 parts of gum arabic, 15 parts of propylene glycol, 20 parts of polyethylene glycol, 4 parts of sodium lauryl sulfate, 0.1 parts of aspartame, 0.1 parts of stevioside, 0.5 parts of sodium citrate, and 20 parts of deionized water;
[0061] The mass of the repairing component accounts for 25% of the total mass of the toothpaste, and the repairing component is the above-mentioned plant-based bioactive glass.
[0062] The toothpaste is prepared by the following steps:
[0063] Step 1, mixing carrageenan, starch, gum arabic, aspartame, stevioside, propylene glycol, polyethylene glycol and deionized water to obtain a first premix;
[0064] Step 2, mixing silicon dioxide with the first premix solution, stirring and heating to 65° C. to obtain a second premix;
[0065] Step 3: Mix and stir the plant extract-modified bioactive glass, sodium dodecyl sulfate and the second premix, continue to add sodium citrate, and stir to obtain toothpaste.
[0066] Example 3
[0067] 1. Preparation of plant extract modified bioactive glass
[0068] The plant extract (the mass ratio of licorice extract to magnolia bark extract is 2:2) was mixed with phosphate buffer and allowed to stand for 35 minutes to obtain a mixed solution with a plant extract concentration of 150 mg / mL; 4 g of bioactive glass (oxide content of SiO2 40 mol%, P2O5 7 mol%, CaO 28 mol%, Na2O 25 mol%) was added to every 100 mL of the mixed solution, and the two were mixed, and then stirred at 40°C for 10 hours to obtain a suspension; the obtained suspension was centrifuged at a speed of 3000 rpm for 5 minutes, and the solid matter obtained was dried to obtain plant extract modified bioactive glass;
[0069] The part of the plant extract modified bioactive glass whose particle size D satisfies 0.5 μm ≤ D < 8 μm is recorded as particle A, the part of the plant extract modified bioactive glass whose particle size D satisfies 8 μm ≤ D < 20 μm is recorded as particle B, and the part of the plant extract modified bioactive glass whose particle size D satisfies 20 μm ≤ D < 50 μm is recorded as particle C;
[0070] By mixing particles A (particle size D50 = 1 μm) with a mass proportion of 50%, particles B (particle size D50 = 12 μm) with a mass proportion of 40%, and particles C (particle size D50 = 45 μm) with a mass proportion of 10%, plant-based bioactive glass (referred to as Elopas plant-based bioactive glass) is obtained.
[0071] 2. Preparation of Toothpaste
[0072] Toothpaste includes basic ingredients and repair ingredients;
[0073] The mass of the basic components accounts for 90% of the total mass of the toothpaste, and the basic components include the following raw materials in parts by weight: 35 parts of calcium carbonate, 5 parts of hydroxyapatite, 0.1 parts of carrageenan, 0.2 parts of gum arabic, 20 parts of glycerin, 10 parts of sorbitol, 15 parts of polyethylene glycol, 2 parts of cocamidopropyl betaine, 2 parts of sodium lauryl sulfate, 0.2 parts of aspartame, 0.2 parts of xylitol, 0.1 parts of saccharin sodium, 1.2 parts of sodium citrate, and 35 parts of deionized water;
[0074] The mass of the repairing component accounts for 10% of the total mass of the toothpaste, and the repairing component is the above-mentioned plant-based bioactive glass.
[0075] The toothpaste is prepared by the following steps:
[0076] Step 1, mixing carrageenan, gum arabic, aspartame, xylitol, saccharin sodium, glycerol, sorbitol, polyethylene glycol and deionized water to obtain a first premix;
[0077] Step 2, mixing calcium carbonate with the first premix solution, stirring and heating to 55° C. to obtain a second premix;
[0078] Step 3: Mix and stir the plant extract-modified bioactive glass, cocamidopropyl betaine, sodium lauryl sulfate and the second premix, continue to add sodium citrate, and stir to obtain toothpaste.
[0079] Example 4
[0080] The difference between this embodiment and embodiment 1 is that the oxide content in the bioactive glass is SiO2 43 mol%, P2O5 12 mol%, CaO 20 mol%, and Na2O 25 mol%; the other steps and conditions are consistent with embodiment 1.
[0081] Example 5
[0082] The difference between this embodiment and embodiment 1 is that the plant extract modified bioactive glass is prepared by the following steps:
[0083] The plant extract (the mass ratio of licorice extract to magnolia bark extract is 3:2) was mixed with phosphate buffer and allowed to stand for 10 minutes to obtain a mixed solution with a concentration of 70 mg / mL; the two were mixed according to the principle of adding 8 g of bioactive glass (oxide content of SiO2 45 mol%, P2O5 8 mol%, CaO 25 mol%, Na2O 22 mol%) per 100 mL of the mixed solution, and then stirred at 35°C for 10 hours to obtain a suspension; the obtained suspension was centrifuged at a speed of 3000 rpm for 5 minutes to obtain a solid substance, which was dried to obtain plant extract modified bioactive glass;
[0084] The other steps and conditions are the same as those in Example 1.
[0085] Example 6
[0086] The difference between this embodiment and embodiment 1 is that the plant extract modified bioactive glass is prepared by the following steps:
[0087] The plant extract (the mass ratio of licorice extract to magnolia bark extract is 3:2) and phosphate buffer are mixed and allowed to stand for 20 minutes to obtain a mixed solution with a concentration of 170 mg / mL; the two are mixed according to the principle of adding 1g of bioactive glass (the oxide content is SiO2 45mol%, P2O5 8mol%, CaO 25mol%, Na2O 22mol%) to every 100mL of the mixed solution, and then stirred at 70°C for 8h to obtain a suspension; the obtained suspension is centrifuged at a speed of 3000rpm for 5min, and the solid matter obtained is dried to obtain plant extract modified bioactive glass;
[0088] The other steps and conditions are the same as those in Example 1.
[0089] Example 7
[0090] The difference between this embodiment and embodiment 1 is that, under the premise that the proportion of the repairing component in the toothpaste remains unchanged, the repairing component also includes a polyamide-amine dendrimer, and the mass ratio of the plant extract modified bioactive glass to the polyamide-amine dendrimer is 1:1;
[0091] The other steps and conditions are the same as those in Example 1.
[0092] Example 8
[0093] The difference between this embodiment and embodiment 1 is that, under the premise that the proportion of the repairing component in the toothpaste remains unchanged, the repairing component also includes a polyamide-amine dendrimer, and the mass ratio of the plant extract modified bioactive glass to the polyamide-amine dendrimer is 5:1;
[0094] The other steps and conditions are the same as those in Example 1.
[0095] Example 9
[0096] The difference between this embodiment and embodiment 1 is that, under the premise that the proportion of the repairing component in the toothpaste remains unchanged, the repairing component also includes a polyamide-amine type dendrimer, and the mass ratio of the plant extract modified bioactive glass to the polyamide-amine type dendrimer is 2:1;
[0097] The other steps and conditions are the same as those in Example 1.
[0098] Example 10
[0099] The difference between this embodiment and embodiment 1 is that, under the premise that the proportion of the repairing component in the toothpaste remains unchanged, the repairing component also includes a polyamide-amine dendrimer, and the mass ratio of the plant extract modified bioactive glass to the polyamide-amine dendrimer is 4:1;
[0100] The other steps and conditions are the same as those in Example 1.
[0101] Comparative Example 1
[0102] The difference between this comparative example and Example 1 is that the toothpaste does not contain plant extract-modified bioactive glass; the other steps and conditions are consistent with Example 1.
[0103] Comparative Example 2
[0104] The difference between this comparative example and Example 1 is that the repair component includes plant extract and bioactive glass in a mass ratio of 1:1, and the repair component is obtained by physically mixing the plant extract and the bioactive glass; the other steps and conditions are consistent with Example 1.
[0105] Comparative Example 3
[0106] The difference between this comparative example and Example 1 is that, for the plant extract modified bioactive glass, the mass proportion of particles with a particle size D satisfying 0.5μm≤D<8μm is 10%, the mass proportion of particles with 8μm≤D<20μm is 60%, and the mass proportion of particles with 20μm≤D<50μm is 30%; the other steps and conditions are consistent with Example 1.
[0107] Test Method
[0108] 1. Test on the effect of strong teeth
[0109] The toothpastes in the above embodiments and comparative examples were tested for their effect on strengthening teeth, and the specific test steps are as follows:
[0110] (1) Tooth sample preparation and artificial demineralization
[0111] 65 healthy and complete bovine premolars were divided into 13 groups, 5 in each group, and ultrasonically cleaned. The 1 / 3 normal glaze surface (clear texture, no white spots, no cracks) in the buccal surface of the crown was selected as the test area using a stereo microscope; the teeth were placed in a 2 mol / L high helium acid solution, taken out after 2 minutes, rinsed with running water, the roots were cut off, polished with fine grinding sandpaper (first 1000 mesh, then 2000 mesh), smoothed, and ultrasonically cleaned for 15 minutes. A 2mm×2mm window area was left at the smooth glaze surface, and the rest was sealed with nail polish and inlay wax to obtain the test sample; the sample was immersed in a demineralization solution with 0.1 mol / L lactic acid and pH 4.1 for 10 hours, taken out and rinsed with running water to obtain the demineralized tooth for standby use.
[0112] (2) Toothpaste sample preparation
[0113] Take 10 g of each toothpaste in Examples 1-10 and Comparative Examples 1-3, add the toothpaste into 150 mL of deionized water, stir evenly to prepare a suspension for later use.
[0114] (3) Remineralization test
[0115] Each group of prepared demineralized teeth is immersed in a toothpaste suspension with a temperature of 37°C (the first group of demineralized teeth is immersed in the suspension made of the toothpaste of Example 1, the second group of demineralized teeth is immersed in the suspension made of the toothpaste of Example 2, and so on), the toothpaste suspension is changed once a day, and the demineralized teeth are immersed for 10 consecutive days. The temperature of the toothpaste suspension is kept at 37°C during the entire immersion process;
[0116] A hardness tester was used to measure the changes in tooth hardness (SMH) before, after and after demineralization, and the hardness recovery value was used to evaluate the effect of toothpaste in improving the hardness of enamel chips.
[0117] The calculation formula for characterizing the microhardness recovery of enamel blocks is as follows:
[0118] Microhardness recovery rate (%) = (SMH after remineralization - SMH after demineralization) / (SMH before demineralization - SMH after demineralization) × 100%. The greater the microhardness recovery percentage, the better the toothpaste's ability to repair demineralized enamel. The results are shown in Table 1.
[0119] 2. Evaluation of mineralization whitening teeth
[0120] The toothpastes in the above embodiments and comparative examples were tested for their mineralization and teeth whitening effects, and the specific test steps are as follows:
[0121] (1) Tooth sample preparation, artificial demineralization and staining
[0122] 65 healthy and complete bovine premolars were divided into 13 groups, 5 in each group, and ultrasonically cleaned. The 1 / 3 normal glaze surface (clear texture, no white spots, no cracks) in the buccal surface of the crown was selected as the test area using a stereo microscope; the tooth was placed in a high helium acid solution with a concentration of 2 mol / L, taken out after 2 minutes, rinsed with running water, the root was cut off, and polished with fine sandpaper (first 1000 mesh, then 2000 mesh), smoothed, and ultrasonically cleaned for 15 minutes. A 2mm×2mm window area was left at the smooth glaze surface, and the rest was sealed with nail polish and inlay wax to obtain the test sample. A clean tempo paper towel was placed under the tooth, fixed at the same location and photographed. A 1mL+200uL box was used for height positioning to take a panoramic shot and a 200u box was used for height positioning to take a local shot. Note that each shot was focused on the middle of the paper towel; open photoshop and use the information function. The middle of the focused paper towel is used as the reference baseline to make L = 90, so as to eliminate the brightness difference caused by sunlight, etc. Each tooth is evenly divided into nine areas using a nine-square grid, and nine points are selected as measurement points; a sample with uniform color is selected for testing to obtain the L value and recorded as L before staining and demineralization;
[0123] The sample was placed in a staining and demineralizing solution containing 8 g / L black tea and a pH value of 4.1. The staining and demineralizing solution covered the tooth surface and the solution was changed every day. When changing the solution, loose attachments on the surface were cleaned with deionized water. The solution was soaked for 5 days to obtain the stained and demineralized teeth for use. The above test process of testing the L value was repeated and recorded as L after staining and demineralization.
[0124] (2) Remineralization test (toothbrushing operation)
[0125] Take 1 g of each toothpaste in Examples 1-10 and Comparative Examples 1-3, and brush your teeth every morning and evening, with each brushing time being no less than 3 min; the demineralized teeth of the first group are brushed with the toothpaste of Example 1, the demineralized teeth of the second group are brushed with the toothpaste of Example 2, and so on); record the L value after brushing, which is recorded as L after remineralization (after brushing).
[0126] Hunter Lab values are measured according to the standards set by the International Commission on Illumination. The Lab system provides a numerical representation of the three-dimensional color space, where L represents the brightness axis, a represents the red-green axis, and b represents the yellow-blue axis. Usually the L axis is most suitable for measuring tooth whiteness.
[0127] △L is used to characterize the whitening ability of toothpaste on enamel. △L=L after remineralization (after brushing)-L after staining and demineralization. The larger the △L, the better the toothpaste's repair and whitening effect on stained and demineralized enamel.
[0128] PCR was used to characterize the effect of toothpaste in removing exogenous tooth staining, PCR = [L after remineralization (after brushing) - L after demineralization by staining] / (L before demineralization by staining - L after demineralization by staining) × 100%; the larger the PCR value, the higher the cleaning ratio, indicating that the cleaning effect of the toothpaste is better.
[0129] Brush your teeth for 60 days and 120 days and record the relevant data, and calculate to obtain the increase in tooth brightness and cleaning ratio after 60 days of brushing and the increase in tooth brightness and cleaning ratio after 120 days of brushing; the results are shown in Table 1.
[0130] 3. Testing of the sealing effect of dentinal tubules
[0131] The toothpastes in the above embodiments and comparative examples were tested for the dentinal tubule sealing effect, and the specific test steps are as follows:
[0132] 1. Model preparation: 65 healthy and complete bovine premolars were collected and divided into 13 groups, 5 teeth in each group. The enamel on the occlusal surface was removed with a diamond needle to expose the dentin. The roots were cut off and placed in an ultrasonic cleaner to remove debris in the dentinal tubules.
[0133] 2. Treatment method: The toothpastes provided in Examples 1-10 and Comparative Examples 1-3 were evenly applied on moistened bovine teeth with exposed dentinal tubules (the first group of demineralized teeth were applied with the toothpaste of Example 1, the second group of demineralized teeth were applied with the toothpaste of Example 2, and so on), simulating brushing, with an application dosage of 2 g / cm 2 After standing for 5 minutes, rinse with distilled water until there is no residue left; repeat this method every 2 hours or more, and after repeating 15 times, rinse with high-pressure water.
[0134] 3. Detection method: The occlusion rate of dentinal tubules was detected by electron microscope at a magnification of 500 times. The results are shown in Table 1.
[0135] 4. Antibacterial performance test
[0136] The antibacterial effect test was carried out on the toothpastes in the above embodiments and comparative examples. The specific test steps are as follows: the test method is carried out according to the antibacterial (inhibitory) test method of 2.1.8 of the "Technical Specifications for Disinfection".
[0137] Preparation of antibacterial tablets: In a clean sterile dish, prepare antibacterial agent original ointment tablets with a diameter of 5 mm and a thickness of no more than 4 mm, in groups of 4 tablets.
[0138] Inoculation of test bacteria: Use a sterile cotton swab to dip a 5×10 5 cfu / ml~5×10 6 cfu / ml test bacterial suspension was evenly applied on the surface of the nutrient agar medium plate for 3 times. The plate should be rotated 60° each time. Finally, the cotton swab was applied around the edge of the plate for one week, the plate was covered, and it was dried at room temperature for 5 minutes.
[0139] Placement of antibacterial agent samples: Place one contaminated plate for each test, and place four test samples of the same test group on each plate. Use sterile tweezers to take the sample and place it on the surface of the plate. The distance between the centers of each sample is more than 25mm, and the distance from the edge of the plate is more than 15mm. After placing, use sterile tweezers to gently press the sample to make it close to the surface of the plate. Cover the plate, place it in a 37℃ incubator, incubate for 24 hours, and observe the results. Use a vernier caliper to measure the diameter of the antibacterial ring, record and calculate the average value.
[0140] The strain used in this test is a common oral pathogen: Streptococcus mutans.
[0141] Evaluation criteria for antibacterial test: when the diameter of the antibacterial ring is greater than 7mm, it is judged to have antibacterial effect; when the diameter of the antibacterial ring is less than or equal to 7mm, it is judged to have no antibacterial effect.
[0142] Table 1
[0143]
[0144]
[0145] In combination with Examples 1-3, Comparative Examples 1-3 and Table 1, it can be seen that the present invention can significantly improve the remineralization effect of toothpaste on demineralized teeth by introducing plant extract-modified bioactive glass into toothpaste, and the microhardness recovery rate of teeth, dentinal tubule closure rate, tooth brightness and cleaning ratio can all be significantly improved; this is because the plant extract-modified bioactive glass can not only form a cyclic chelate that is poorly soluble in acid to reduce the effect of demineralization on the volume of tooth gaps, but also inhibit the activity of matrix proteases to promote the process of bionic remineralization and improve the binding stability of rivet-shaped crystals in the gaps. Furthermore, by controlling the particle size distribution of plant extract modified bioactive glass, small particles of plant extract modified bioactive glass can be sealed into the dental tubules and generate remineralization products that combine with the remineralization products on the tooth surface; large particles of plant extract modified bioactive glass have good strength and can be used as an abrasive to clean the surface of demineralized teeth, reduce exogenous pigment deposition, and improve the cleaning effect on teeth; the above two repair effects make the surface of demineralized teeth smooth, thereby significantly improving the whiteness of demineralized teeth. Finally, plant extract modified bioactive glass has excellent antibacterial effects, can improve the health of oral mucosa, and together with the remineralization effect on teeth, significantly play an effect of improving oral health.
[0146] In combination with Example 1, Example 4 and Table 1, it can be seen that by controlling the content of oxides in the bioactive glass to be within a reasonable range, the calcium-phosphorus ratio of the plant extract-modified bioactive glass after dissolution can be adjusted, thereby facilitating the remineralization process and generating a sufficient amount of hydroxyapatite to improve the repair effect of the toothpaste on demineralized teeth.
[0147] In combination with Example 1, Examples 5-6 and Table 1, it can be seen that the plant extract modified bioactive glass prepared by the method of the present application can load a sufficient amount of licorice extract and magnolia bark extract and introduce polyhydroxyl groups and hydrogen bonds into the system, thereby helping to obtain a toothpaste with good demineralized tooth repair effect and good antibacterial performance.
[0148] In combination with Example 1, Examples 7-10 and Table 1, it can be seen that by introducing polyamide-amine dendritic polymers into the repairing ingredients and controlling the mass ratio of polyamide-amine dendritic polymers to the plant extract modified bioactive glass within a reasonable range, the remineralization effect of toothpaste on demineralized teeth can be further improved, and the microhardness recovery rate, dentinal tubule closure rate and whiteness of the teeth can be further improved; this is because the introduction of an appropriate amount of polyamide-amine dendritic polymers can work together with the plant extract modified bioactive glass to adjust the morphology and size of hydroxyapatite so that it can more easily enter the gaps of demineralized teeth, improve the closure rate of the dental tubules after using the toothpaste, and can further improve the strength of the remineralization product, thereby helping to improve the repair effect of the toothpaste on demineralized teeth; further, the polyamide-amine dendritic polymers can also interfere with the formation process of bacterial biofilms, thereby working together with the plant extract modified bioactive glass to significantly improve the antibacterial performance of the toothpaste.
[0149] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A plant-based bioactive glass, characterized in that: Includes plant extract modified bioactive glass; The particle size D of the plant extract modified bioactive glass meets the following conditions: the mass proportion of particles with a particle size D satisfying 0.5 μm ≤ D < 8 μm is 40%-50%, the mass proportion of particles with a particle size D satisfying 8 μm ≤ D < 20 μm is 30%-40%, and the mass proportion of particles with a particle size D satisfying 20 μm ≤ D < 50 μm is 10%-20%; The plant extract modified bioactive glass is prepared by a method comprising the following steps: mixing the plant extract with a phosphate buffer solution and then standing the mixture, adding the bioactive glass to the obtained mixed solution, stirring the mixture to obtain a suspension, and drying the solid matter obtained after solid-liquid separation of the suspension to obtain the plant extract modified bioactive glass; The plant extract comprises liquorice extract and magnolia bark extract; the mass ratio of the liquorice extract to the magnolia bark extract is 2-5:1-2.
2. The plant-based bioactive glass according to claim 1, characterized in that: The concentration of the plant extract in the mixed solution is 80-150 mg / mL; 2.5-4 g of the bioactive glass is added to every 100 mL of the mixed solution; the temperature during the stirring process is 40-60° C., and the duration of the stirring process is 5-10 hours.
3. The plant-based bioactive glass according to claim 1, characterized in that: The bioactive glass has the following contents expressed as oxides: SiO2 40 mol%-50 mol%, P2O5 5 mol%-10 mol%, CaO2 2 mol%-30 mol%, Na2O 22 mol%-30 mol%.
4. An oral care product containing plant-based bioactive glass, characterized in that: It includes a basic component and a repair component, wherein the mass of the repair component accounts for 10%-25% of the total mass of the oral care product; The repairing component comprises the plant extract modified bioactive glass as claimed in any one of claims 1-3.
5. The oral care product containing plant-based bioactive glass according to claim 4, characterized in that: The repairing component also includes polyamide-amine type dendrimer.
6. The oral care product containing plant-based bioactive glass according to claim 5, characterized in that: Taking the repair component as a benchmark, the mass ratio of the plant extract modified bioactive glass to the polyamide-amine type dendrimer in the repair component is 2-4:
1.
7. The oral care product containing plant-based bioactive glass according to claim 4, characterized in that: Based on the basic components, the basic components include the following raw materials in parts by weight: 0.3-0.6 parts of thickener, 35-45 parts of moisturizer, 3-4 parts of foaming agent, 0.2-0.5 parts of sweetener, 0.5-1.2 parts of neutralizer, 20-35 parts of deionized water, and 2-5 parts of enhancer.
8. The oral care product containing plant-based bioactive glass according to claim 7, characterized in that: The thickener includes at least one of carrageenan, carboxymethyl cellulose, starch, xanthan gum, gum arabic, gum karaya, and carrageenan; the moisturizer includes at least one of glycerin, sorbitol, propylene glycol, polyethylene glycol, and polypropylene glycol; the foaming agent includes at least one of cocamidopropyl betaine and sodium lauryl sulfate; and the enhancer includes hydroxyapatite.
9. The oral care product containing plant-based bioactive glass according to any one of claims 4 to 8, wherein the oral care product comprises any one of toothpaste, tooth protection paste, oral antibacterial paste, oral desensitizing paste, oral anti-caries paste, and tooth desensitizer.
10. The oral care product containing plant-based bioactive glass according to claim 9, characterized in that: Based on the basic component, the basic component also includes 20-35 parts of abrasive; the abrasive includes at least one of silicon dioxide and calcium carbonate.